A Glimpse on Sectoral Convergence of Productivity Levels - Gerald Müller (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2001)
This paper examines the presence of sectoral convergence of labor productivity between 14 OECD countries. Using the OECD International Sectoral Data Base (ISDB), the paper looks at the developments within 12 distinct sectors during the period 1970-1995. The change of the coefficients of variance suggests that there is strong sectoral convergence within most service sectors while the evidence of convergence for Manufacturing as well as for Communication is rather weak. These findings are in line with most studies undertaken on this subject so far. It is concluded that economic theories at hand to explain growth and convergence (or divergence respectively) are of different importance for the sectors concerned. While models of the New Growth Theory seemed to be useful to explain growth mechanisms within Manufacturing and Communication, traditional models seemed to apply to most other sectors.
urn:nbn:de:gbv:3:2-19100
Keywords: D24; F15; F43; O41; O57; 330; Arbeitsproduktivität; Branchenentwicklung; Entwicklungskonvergenz; Vergleich; Schätzung; OECD-Staaten